Bank Lending in Turkey : Effects of Monetary and Fiscal Policies - Aydin, Burcu (IMF Working Papers; Working Paper ;, 2010)
The period following the 2000-01 crisis was marked by a successful disinflation program sustained through inflation targeting and fiscal discipline in Turkey. This paper studies the impact of monetary and fiscal policies on credit growth during this period. Using quarterly bank-level data covering 2002-08, we find evidence that liquidity-constrained banks have sharper decline in lending during contractionary monetary policies and that crowding-out effect disappears more for banks with a retail-banking focus when fiscal policies are prudent.The results are statistically weak, suggesting that bank lending channel is not strong in Turkey and government finances has limited direct impact on credit.